Spanlastics for Targeted CNS Drug Delivery - Rajaa A. Dahash; Mowafaq M.Ghareeb (Iraqi Journal of Pharmaceutical Sciences, 2025)
Numerous pharmacological compounds now on the market are ineffective in treating brain disorders ,they are not getting to the brain with the concentration required to have a pharmacological effect. Since there are many barrier as blood brain barrier (BBB), P-glycoprotein (an active efflux transporter), and specific enzymatic activity are some of the mechanisms that protect the brain from harmful circumstances. These systems, in particular BBB hinder therapeutic interventions of many medications . Thus, the majority of the medicine cannot give the desired effect because they cannot penetrate the brain, so they are useless in the treatment of brain illnesses . As a result, numerous Therefore, strategies that could enhance drug delivery to the brain. Thus, the vesicular medication delivery devices have made important advancements in nanotechnology. These systems are useful for avoiding a number of problems with traditional dosage forms, liposomes, nanoparticles and spanlastic are proving to be more effective. Spanlastics are surfactant-based elastic vesicular drug delivery method that traps the medication in the core cavity as a bilayer, they are amphiphilic in nature and deliver both hydrophilic and hydrophobic medications . Surface active agent , edge activator and ethanol are used to prepare the spanlastic and many methods can be used to prepare of these vesicles .